(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This qualitative research purposed to explore some of the issues that face English language learners during learning English which negatively affect their learning. In addition, it aimed to identify the best strategies for improving low proficiency students in English from the perspectives of English teachers. The study was conducted on 17 middle school English teachers who were randomly chosen to participate, and 35 of their low proficiency students. The data collection consisted of open-ended questionnaire for the students and semi-structured interview for the teachers. The results of the study indicated that ‏there are many issues that may affect the learning of English language learners with low proficiency in English. These issues include: lack of listening and speaking tests, teaching method is not communicative, students’ attitude towards English, lack of the necessary facilities, and role of the teachers in improving speaking skills. Further, the findings of the analysis indicated some of the best strategies for improving middle school students “low proficiency in English” from the teachers’ perspectives. Those strategies consisted of teacher-centered learning method, presentation method, seminar method, and student-centered learning method. In contrast, another result showed that teachers agreed about the lecture method to be the least beneficial strategy for improving students’ English.